Coagulation in liver toxicity and disease: Role of hepatocyte tissue factor - Kopec, Anna K. (2014)
The liver is the primary source of a number of circulating coagulation factors, and acute liver injury and chronic liver disease are each associated with alterations in blood coagulation. Current views of the connection between liver injury and coagulation extend beyond the impact of liver disease on synthesis of coagulation factors to include a role for coagulation factor activity in the initiation and progression of liver disease. Mechanisms of coagulation initiation in liver disease are not completely understood. Compared to other tissues, liver expresses very low levels of tissue factor (TF). Recent studies indicate that expression of TF by hepatocytes comprises the majority of liver procoagulant activity, and that hepatocyte TF activates coagulation induced by liver injury. This review will briefly cover the expression and regulation of TF by hepatocytes, the role of TF in coagulation triggered by liver toxicity, and the contribution of coagulation activity to the progression of liver disease.